(untitled) (Research, Society and Development, 2024)
In this context, we explore surgical techniques that use connective tissue grafts to treat gingival recessions. These approaches aim to solve aesthetic problems and improve gingival function. Considerations about biological factors that influence the predictability of root coverage are fundamental to choosing the best therapeutic alternative. There are important differences between the different surgical techniques available, with the aim of minimizing surgical trauma and obtaining better results. The connective tissue graft demonstrates significant clinical gains in terms of insertion, keratinized tissue and root coverage, making it a viable and predictable option for the treatment of Miller Class I and II gingival recessions. Even for Miller Class III recessions where root coverage is limited, treatment may be considered, especially to increase keratinized tissue. Objective: To examine, based on recent literature, the scientific evidence related to the feasibility of using free gingival grafts in the management of gingival recession. Methodology: A literature review was carried out based on studies published in the Scielo, Scholar Google and PubMed databases. Results: Gingival recession is characterized by the apical retreat of the gingival margin, a phenomenon associated with various conditions and diseases, resulting in the loss of clinical attachment.